Reaction rate of the 13C(α, n)16O neutron source using the ANC of the -3 keV resonance measured with the THM. Issue 1 (January 2016) - La Cognata, M; Spitaleri, C; Trippella, O; Kiss, G G; Rogachev, G V; Mukhamedzhanov, A M; Avila, M; Guardo, G L; Koshchiy, E; Kuchera, A; Lamia, L; Puglia, S M R; et al.
Abstract: The s -process is responsible of the synthesis of most of the nuclei in the mass range 90 ≤ A ≤ 208. It consists in a series of neutron capture reactions on seed nuclei followed by β -decays, since the neutron accretion rate is slower than the β -decay rate. Such small neutron flux is supplied by the 13 C( α, n ) 16 O reaction. It is active inside the helium-burning shell of asymptotic giant branch stars, at temperatures < 10 8 K, corresponding to an energy interval of 140–230 keV. In this region, the astrophysical S ( E )-factor is dominated by the −3 keV sub-threshold resonance due to the 6.356 MeV level in 17 O. In this work, we have applied the Trojan Horse Method (THM) to the 13 C( 6 Li, n 16 O) d quasi-free reaction to extract the 6.356 MeV level resonance parameters, in particular the asymptotic normalization coefficient . A preliminary analysis of a partial data set has lead to, slightly larger than the values in the literature. However, the deduced 13 C( α, n ) 16 O reaction rate is in agreement with most results in the literature at ∼ 10 8 K, with enhanced accuracy thanks to our innovative approach merging together ANC and THM.